2020
DOI: 10.36076/ppj.2020/23/s239
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Superiority of Epidural Injections with Lidocaine with Steroids Compared to Without Steroids in Spinal Pain: A Systematic Review and Meta-Analysis

Abstract: Background: Multiple randomized controlled trials (RCTs) and systematic reviews have been conducted to summarize the evidence for administration of local anesthetic (lidocaine) alone or with steroids, with discordant opinions, more in favor of equal effect with local anesthetic alone or with steroids. Objective: To evaluate the comparative effectiveness of lidocaine alone and lidocaine with steroids in managing spinal pain to assess superiority or equivalency. Study Design: A systematic review of RCTs assessin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…The use of interlaminar epidural corticosteroid injections (CESI) for cervical radicular pain was evaluated in a systematic review, which demonstrated Level II evidence for the effectiveness of interlaminar CESI with local anesthetic with or without steroids based on multiple RCTs 64 . A meta‐analysis failed to demonstrate benefit for the addition of corticosteroids to local anesthetic in interlaminar CESI but this conclusion was based on few available studies and a lack of homogeneity in the included RCTs 65 . The American Society of Interventional Pain Physicians (ASIPP) reported level I evidence for interlaminar CESI with a strong recommendation for long‐term effectiveness with repeated injections 66 .…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of interlaminar epidural corticosteroid injections (CESI) for cervical radicular pain was evaluated in a systematic review, which demonstrated Level II evidence for the effectiveness of interlaminar CESI with local anesthetic with or without steroids based on multiple RCTs 64 . A meta‐analysis failed to demonstrate benefit for the addition of corticosteroids to local anesthetic in interlaminar CESI but this conclusion was based on few available studies and a lack of homogeneity in the included RCTs 65 . The American Society of Interventional Pain Physicians (ASIPP) reported level I evidence for interlaminar CESI with a strong recommendation for long‐term effectiveness with repeated injections 66 .…”
Section: Treatmentsmentioning
confidence: 99%
“…64 A meta-analysis failed to demonstrate benefit for the addition of corticosteroids to local anesthetic in interlaminar CESI but this conclusion was based on few available studies and a lack of homogeneity in the included RCTs. 65 The American Society of Interventional Pain Physicians (ASIPP) reported level I evidence for interlaminar CESI with a strong recommendation for long-term effectiveness with repeated injections. 66 The effectiveness of interlaminar CESI was compared to transforaminal CESI in 108 patients with axial pain due to cervical disk herniation.…”
Section: Interventional Pain Managementmentioning
confidence: 99%
“…Over the years, literature has provided discordant conclusions of the clinical and cost-utility of epidural procedures, even though extensive literature, including systematic reviews, randomized controlled trials, cost-utility analysis, and guidelines,35–58 have shown appropriate evidence. Discordant conclusions are based on the lack of agreement between proponents and opponents of the effectiveness and indications, with proponents emphasizing inappropriate conclusions as the basis of discordant results.…”
mentioning
confidence: 99%
“…Systematic reviews have shown showed that there was no superiority of epidural steroids plus local over local anesthetic alone. 3 In addition, epidural injection of sodium chloride solution has been shown to be not a true placebo as it was equally effective as steroids. 4 Cochrane may be propagating a mistake that has the potential to harm patients by limiting access on the basis of flawed interpretation of data.…”
mentioning
confidence: 99%
“…Recently, Shanthanna et al 2 in a systematic review of all the studies available showed steroids do not provide any significant additional relief than local anesthetic injections alone. Systematic reviews have shown showed that there was no superiority of epidural steroids plus local over local anesthetic alone 3 . In addition, epidural injection of sodium chloride solution has been shown to be not a true placebo as it was equally effective as steroids 4 .…”
mentioning
confidence: 99%